Stories of the “good father”: The role of fatherhood among incarcerated men in Mexico - Sandberg, Sveinung (Punishment & society, 2022)
This study examines the role of fatherhood for incarcerated men in Mexico, based on repeated life-story interviews with twelve men. We distinguish between their descriptions of fatherhood in the past and present and how they imagine the future, and explore how fathers describe their relationship with their children. The incarcerated men idealize the past with their children or tell stories of how they have changed from being “bad” to “good” fathers. They emphasize how they are still able to protect and educate their children from prison, reflecting widespread values of fatherhood. They admit that fathering while incarcerated is difficult and hope that things will be better in the future. In line with previous research on fathers in prison, we argue that storytelling of being “good fathers” is a way of projecting “normalcy”, using one of the few gendered resources available, and is an escape from the harsh realities of prison life. Following insights from narrative criminology and desistance studies, we further argue that their stories of fatherhood can be a resource for reintegration into society. Finally, we suggest that inmates’ emphasis on involved fatherhood might reflect diffusing narratives, ideals, and norms of parenting.